2009
DOI: 10.1111/j.1600-0765.2008.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone administration may modulate periodontal tissue levels of interleukin‐6, matrix metalloproteinase‐2 and matrix metalloproteinase‐9 in experimental periodontitis

Abstract: These data suggest that intermittent administration of parathyroid hormone can down-regulate the expression of biomarkers responsible for connective tissue breakdown and bone resorption, and potentially affect alveolar bone resorption activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The present authors have reported previously that intermittent hPTH 1‐34 administration can protect against bone loss from periodontitis in rats 9‐11 . In addition, hPTH 1‐34 administration can also promote bone gain in alveolar bone affected by periodontitis in humans 12 .…”
supporting
confidence: 49%
“…The present authors have reported previously that intermittent hPTH 1‐34 administration can protect against bone loss from periodontitis in rats 9‐11 . In addition, hPTH 1‐34 administration can also promote bone gain in alveolar bone affected by periodontitis in humans 12 .…”
supporting
confidence: 49%
“…MMP9 activity increases significantly in the gingival tissues of patients with periodontitis 24 . Such an MMP9 increase was observed in ligature 16,25 but not in GAV models 26 . CATB is involved in physiologic and pathologic tissue remodeling and cell apoptosis 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Using imaging software, ‡‡‡‡ TRAP‐positive cells were counted on the alveolar bone crest surface at the palatal root and the mesial and distal furcation aspects of the first molar using standardized views. The number of TRAP‐positive cells was divided by the bone soft connective tissue linear surface length 25 …”
Section: Methodsmentioning
confidence: 99%
“…21 Aliquots of gingival tissue homogenates containing the same protein amount were run under non-reducing conditions without heat denaturation onto 10% sodium dodecyl sulfate polyacrylamide gels (SDS-PAGE) co-polymerized with 1.6 mg/mL of gelatin **** as substrate. After SDS-PAGE, the gels were washed twice in 2% Triton X-100 for 30 min each, and then the gels were incubated overnight in activation buffer (50 mM Tris-HCl, pH 7.4, 5 mM CaCl 2 ) for 16 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%